2020
DOI: 10.1523/eneuro.0412-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Mitf Links Neuronal Activity and Long-Term Homeostatic Intrinsic Plasticity

Abstract: Neuroplasticity forms the basis for neuronal circuit complexity and differences between otherwise similar circuits. We show that the microphthalmia-associated transcription factor (Mitf) plays a central role in intrinsic plasticity of olfactory bulb (OB) projection neurons. Mitral and tufted (M/T) neurons from Mitf mutant mice are hyperexcitable, have a reduced A-type potassium current (I A) and exhibit reduced expression of Kcnd3, which encodes a potassium voltage-gated channel subunit (Kv4.3) important for g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…While two copies of Mitf are required for a normal number of MCs, this suggests a tissue-dependent Mitf dosage effect or defects in maintaining MCs in heterozygotes. This is in accordance with known haploinsufficiency in Mitf mutant mice (Harris et al, 2018;Atacho et al, 2020;Han et al, 2020). Increased inflammation is central to CNS pathologies.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While two copies of Mitf are required for a normal number of MCs, this suggests a tissue-dependent Mitf dosage effect or defects in maintaining MCs in heterozygotes. This is in accordance with known haploinsufficiency in Mitf mutant mice (Harris et al, 2018;Atacho et al, 2020;Han et al, 2020). Increased inflammation is central to CNS pathologies.…”
Section: Discussionsupporting
confidence: 85%
“…MITF is a basic helix-loop-helix leucine zipper transcription factor that plays a critical role in the development of many cell types (Hemesath et al, 1994;Steingrimsson et al, 2004), including melanocytes, retinal pigment cells, osteoclasts, and a subpopulation of CNS neurons (Nakayama et al, 1998;Steingrimsson et al, 2002;Gudjohnsen et al, 2015;Atacho et al, 2020). The Mitf gene has been shown to be both important for the generation (Kitamura et al, 2002;Sasaki et al, 2016;Ingason et al, 2019) and function of MCs (Morii et al, 1996(Morii et al, , 1997Nechushtan and Razin, 2002;Paruchuru et al, 2022).…”
Section: The Mitf Gene Is Required For Mast Cell Generation and Functionmentioning
confidence: 99%
“…In accordance with these results, gene MITF (melanocyte inducing transcription factor) was upregulated by 2.5-fold in NR neurons treated with VPA compared to CTL neurons (padj <0.0076). MITF was recently described as a regulator of neuronal activity by transcriptional activation of Kv4.3 potassium channel in olfactory bulb projection neurons [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we found that treatment of NR neurons with VPA caused a change in transcription of the genes involved in synaptic activity and voltage-gated channels. Interestingly two of these genes, MITF and KCNH3 , encode regulators of excitability [ 70 , 71 ]. This study and our previous studies [ 43 , 44 ] showed that hyperexcitability of BD DG-like neurons was a reproducible phenotype that correlated with clinical response of patients to medication.…”
Section: Discussionmentioning
confidence: 99%
“…MITF has emerged as a key regulator of proliferation, differentiation, cell cycle, and survival of melanocytes and melanoma cells (reviewed in Goding & Arnheiter, 2019). It also affects mast cells, retinal pigment epithelium (RPE) and osteoclast development and in addition plays a role in olfaction as well as in circadian regulation of gene expression (Atacho et al, 2020; Malcov‐Brog et al., 2018; Morii et al., 1996; Shibahara et al., 2000; Weilbaecher et al., 2001). In humans, MITF mutations have been linked to Tietz syndrome (Amiel, Watkin, Tassabehji, Read, & Winter, 1998; Smith, Kelley, Kenyon, & Hoover, 2000), Waardenburg syndrome type 2A (Tassabehji, Newton, & Read, 1994) as well as the more serious COMMAD syndrome observed in individuals carrying MITF mutations on each of the two chromosomes (George et al., 2016).…”
Section: Introductionmentioning
confidence: 99%